Case-based decision-making approach to false lumen occlusion in ruptured chronic type B aortic dissection - Noor Hamo, MBBS; Jun Jie Ng, MBBS, FRCS; Lukla Biasi, PhD; Prakash Saha, BSc(Hons), MBBS, PhD, FRCS; Said Abisi, MD, MSc, FRCS; Hany Zayed, MD, MSc, FRCS (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
Ruptured chronic type B aortic dissection (TBAD) is a life-threatening emergency requiring prompt intervention. A 65-year-old woman with chronic TBAD presented with severe chest and epigastric pain. Computed tomography showed a ruptured false lumen (FL) at the proximal descending thoracic aorta. Emergency thoracic endovascular aortic repair sealed the primary entry tear, but haemodynamics instability owing to retrograde FL perfusion required urgent FL occlusion using a custom-made Candy Plug. She recovered with postoperative management including delayed hemothorax drainage. This case highlights a stepwise approach and the importance of further research on optimal timing and strategy for FL occlusion in ruptured chronic TBAD.